Perlindungan Hukum Merek di Jaringan Internet dalam Undang-undang Nomor 15 Tahun 2001 tentang Merek - Cristiani, Th Anita (Jurnal Hukum IUS QUIA IUSTUM, 2018)
The 2001 Trade Mark Acthas not arrangedabout trademarkprotection in cyberspace. Therefore it is important to form special regulation on trade mark protection in cyber space.